Good agricultural practices for ware potato production in Cameroon: Demonstration guide - Harahagazwe, D.; Atieno, E.; Schulte-Geldermann, Elmar; Kromann, P.; Mafouo, H.; Anagho, R.; Schuffenhauer, A.; Sossou, L.; Breitenstein, A.; Festus, K.A. (Deutsche Gesellschaft für Internationale Zusammenarbeit, 2019)
This guide is a complementary support tool to the training materials for ware potato production. Therefore, it is not meant to be used alone. It helps the trainer to organize and facilitate hands- on training in the field. It comprises three demonstration protocols: (i) crop husbandry, (ii) positive selection and (iii) small plot technique. For each demo, the guide provides responses to the following questions: What, Why, When, For how long, With what and How.